Nutritional intervention is promising in alleviating liver injury during tuberculosis treatment: a review - Fu, Yujin; Du, Xianfa; Cui, Yingchun; Xiong, Ke; Wang, Jinyu (Frontiers in Nutrition, 2023)
Liver injury is a main adverse effect of first-line tuberculosis drugs. Current management of tuberculosis-drug-induced liver injury (TBLI) mainly relies on withdrawing tuberculosis drugs when necessary. No effective treatment exists. Various nutrients and functional food ingredients may play a protective role in TBLI. However, a comprehensive review has not been conducted to compare the effects of these nutrients and functional food ingredients. We searched Pubmed and Web of Science databases from the earliest date of the database to March 2023. All available in-vitro, animal and clinical studies that examined the effects of nutritional intervention on TBLI were included. The underlying mechanism was briefly reviewed. Folic acid, quercetin, curcumin, Lactobacillus casei, spirulina and Moringa oleifera possessed moderate evidence to have a beneficial effect on alleviating TBLI mostly based on animal studies. The evidence of other nutritional interventions on TBLI was weak. Alleviating oxidative stress and apoptosis were the leading mechanisms for the beneficial effects of nutritional intervention on TBLI. In conclusion, a few nutritional interventions are promising for alleviating TBLI including folic acid, quercetin, curcumin, L. casei, spirulina and M. oleifera, the effectiveness and safety of which need further confirmation by well-designed randomized controlled trials. The mechanisms for the protective role of these nutritional interventions on TBLI warrant further study, particularly by establishing the animal model of TBLI using the tuberculosis drugs separately.